Physical Exercise for Late‐Life Depression: Customizing an Intervention for Primary Care. Issue 2 (21st November 2016) - Zanetidou, Stamatula; Belvederi Murri, Martino; Menchetti, Marco; Toni, Giulio; Asioli, Fabrizio; Bagnoli, Luigi; Zocchi, Donato; Siena, Matteo; Assirelli, Barbara; Luciano, Claudia; Masotti, Mattia; Spezia, Carlo; et al.
Abstract : Objectives: To identify which individual‐ and context‐related factors influence the translation into clinical practice of interventions based on physical exercise (PE) as an adjunct to antidepressants (AD) for the treatment of late‐life major depression (LLMD). Design: Secondary analysis of a randomized controlled trial. Setting: Primary care with psychiatric consultation‐liaison programs (PCLPs)—organizational protocols that regulate the clinical management of individuals with psychiatric disorders. Participants: Individuals aged 65 and older with major depression according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (N = 121). Intervention: Participants with LLMD were randomized to AD (sertraline) or AD plus PE (AD + PE). Measurements: Participant characteristics that were associated with greater effectiveness of AD + PE (moderators) were identified, and effect sizes were calculated from success rate differences. Whether the characteristics of the study setting influenced participant flow and attendance at exercise sessions was then explored, and primary care physicians (PCPs) were surveyed regarding their opinions on PE as a treatment for LLMD. Results: The following participant characteristics were associated with greater likelihood of achieving remission from depression with AD + PE than with AD alone: aged 75 and older (effect size 0.32), polypharmacy (0.35), greater aerobic capacity (0.48), displaying psychomotor slowing (0.49), and less‐severe anxiety (0.30). The longer the PCLP had been established at a particular center, the more individuals were recruited at that center. After participating in the study, PCPs expressed positive views on AD + PE as a treatment for LLMD and were more likely to use this as a therapeutic strategy. Conclusions: The combination of PE and sertraline could improve the management of LLMD, especially when customized for individuals with specific clinical features. Liaison programs might influence the implementation of similar interventions in primary care, and PCPs viewed them positively.